A case of mucopolysaccharidosis type VI in Indian family: importance of clinical characteristics, urinary GAG and enzyme assay in diagnosis of mucopolysaccharidosis - Ali, Mohammad Amir; Maheshwari, Shivangi; Mohapatra, Mrunmay Das; Dash, Dillip Kumar (International Journal of Contemporary Pediatrics, 2025)
Mucopolysaccharidosis (MPS) are hereditary progressive disease caused by mutations in genes coding for lysosomal enzymes essential to breakdown GAG. The inadequate degradation process leads to accumulation GAG in lysosome of diverse tissues, which interfere with cell functioning and leads to characteristic patterns of clinical, radiologic and biochemical problems. Patient appears to be healthy at birth and, symptoms start about 2-3 years of age. Clinical characteristics, radiographic findings, and notably enzyme assays have allowed us to make a clear diagnosis in these situations. There are extremely few cases of MPS VI reported in India. Here we are reporting a case of 14 yr. old female patient with a combination of clinical, radiological and biochemical characteristics confirmed as a case of MPS type VI. This example illustrates that atypical clinical symptom, such as growth failure, coarse facial features, and joint difficulties, are key pointers for further investigations linked to MPS disease. However, in low- and middle-income countries, it is difficult to make a definite diagnosis of one of the MPS due to insufficient enzyme assay.